Hi. Hayyun as a hero figure of Tolitoli indigenous people’s revolution: An educational exploratory study - H. Hamna; Muh. Khaerul Ummah BK; Moh. Wahyuddi; Syaiful Hidayat; Nurul Asma; Karmila Risa Rahmawati (Research and Development in Education (RaDEn), 2024)
Historical knowledge in today's era is important because by studying history we can find out the background of the formation of a country and important event in the past, and from history we can learn inspiring stories of heroes in fighting for the independence of a region. The purpose of this study is to explore Hi's life and struggles. Hi. Hayyun as a Tolitoli people's revolutionary, as well as identifying the educational implications of his story for history education for the people of Tolitoli. The method used in this study is qualitative descriptive with a historical-contextualistic approach based on characterization studies. Data collection techniques are observation, interviews and documentation studies. The data analysis technique used is the Milles and Huberman model, including presenting information on historical events, sorting information, verifying the truth of information and drawing conclusions. The subject of the study was the Hi. Hayyun whose information excavation involved historian Hi. Hayyun, while the supporting information involved 142 student respondents who studied at Tolitoli. The results of this study found the fact that the local people lack knowledge about the history of heroes in their area and tried to explore the educational values behind Hi's history. Hi. Hayyun as a hero figure in Tolitoli. The implication of the findings of this research is that it is expected to be the content of history learning materials within the scope of local content subjects in elementary schools, including being able to be used as a cluster of Natural Sciences and Social Sciences subjects in the Merdeka Curriculum.